Effect of low-temperature gas-cooled electrode on the performance of EDM process. Issue 1 (September 2016) - Li, L.; Bi, F.; Feng, L.; Bai, X.
Abstract This article investigated on the cooling effect of cold nitrogen-air mixed gas on copper electrode during electrical discharge machining of W6 Mo5 Cr4 V2 high-speed steel. Material removal rate (MRR), electrode wear (EW), and electrode wear rate (EWR) were observed to evaluate the cooling effect. Temperature was the controllable variable under the set process parameters. Results show that the MRR of the workpiece changes slightly when the electrode was cooled above −80 °C. EW decreases with the decrease in temperature. Relative electrode wear (REW) decreases with the decrease in temperature when the cooled temperature is above −80 °C. With electrode cooling, metal that sputtered onto the electrode surface is less under low temperatures. Temperature below −80 °C may cause cracks on the surface of the workpiece.